Kewenangan Pejabat Pembuat Akta Tanah (PPAT) Dalam Proses Jual Beli Tanah - . Baharudin (Universitas Bandar Lampung (UBL), 2014)
Land Deed Official, hereinafter referred to PPAT, is a public official who is authorized to make the authentic deeds of certain legal acts concerning land rights or Ownership Rights Unit of the Flats. The problem in this paper is how to ensure legal certainty PPAT role in the sale and purchase of land, the legal consequence of the land purchase agreement made before the Land Deed Official (PPAT) is the emergence of the obligations and rights between the parties, the seller and buyer as well as the shift of of land property which is the object of buying and selling.